THE IMMUNOGLOBULIN SUPERFAMILY - Jones, E (1993)
The steady flow of fresh data on antibody structure and interactions has continued. Recent results have also extended the scope of the available structural information to cover other members of the immunoglobulin superfamily. This review highlights the new perspectives on the structure and functions of the immunoglobulin fold which have emerged from the latest studies.